Churg-Strauss vasculitis and ascaris infection. Issue 5 (May 1990) - Chauhan, A; Scott, D G; Neuberger, J; Gaston, J S; Bacon, P A
Abstract : A patient with Churg-Strauss vasculitis presenting with mononeuritis multiplex, who developed obstructive jaundice, is described. On investigation the jaundice proved to be due to ascaris infestation. As the immune abnormalities associated with ascaris infection are also typical of those seen in the Churg-Strauss syndrome it is speculated that the vasculitis occurred because of a failure to regulate the anti-ascaris immune response.